Regulatory emotional self-efficacy and anxiety in times of pandemic: a gender perspective - Esther Cuadrado; Manuel Rich-Ruiz; Tamara Gutiérrez-Domingo; Bárbara Luque; Rosario Castillo-Mayén; Joaquín Villaécija; Naima Z. Farhane-Medina (Health Psychology and Behavioral Medicine, 2023)
ABSTRACTObjectives: The COVID-19 pandemic and resultant lockdown and containment measures have instigated substantial changes in our daily lives and have affected many people’s mental health. This paper reports two studies exploring gender-based differences with regard to the impact of COVID-related confinement on individuals’ self-efficacy to regulate negative emotions (RESE-NE) and anxiety.Methods: Study 1 (cross-sectional; 269 participants; 52% women) explored the evolution of RESE-NE and anxiety. To this end, participants assessed their status at two time points: a retrospective assessment of the period before confinement in Spain, and a current assessment during confinement. Study 2 (longitudinal; 114 participants; 72.2% women) explored the evolution of the variables by adding a post-confinement time point and analyzed the mediating role of RESE-NE in the positivity–anxiety and resilience–anxiety relationships.Results: The results confirmed that: (a) RESE-NE decreased and anxiety increased more among women than among men during confinement (Study 1); (b) women recovered their pre-pandemic levels of mental health more slowly than did men following confinement; and (c) the mediating role of RESE-NE could be observed in the two relationships under analysis.Conclusion: In practical terms, the research highlights the need to pay special attention to women undergoing mental health interventions related to the COVID-19 pandemic, as well as to the differential burden that the pandemic may entail for men and women and to the contrasting social roles traditionally attributed to them. From the gender differences identified, it is possible to infer how stereotypes and social roles influence the behavior and mental health of men and women, leading them to cope differently with stressful situations such as confinement.